(untitled) (The Conference Hub, 2025)
The use of drains in surgical practice is a long-established and time-tested approach, yet it still retains certain “delicate aspects” that require attention. Drains serve to evacuate exudate from wounds, remove purulent contents, and reduce pressure. However, the rapid and persistent colonization of drain surfaces by microorganisms represents one of the most common and challenging complications encountered in surgical practice.